Disease Gene Identification Methods and Protocols - DiStefano, Johanna K.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Recent efforts to characterize genetic variation in the human genome, coupled with the rapidly developing field of genomics, have lead directly to the development of new and innovative approaches to the identification of genes contributing to complex human diseases. In Disease Gene Identification: Methods and Protocols, expert researchers in the field provide up-to-date molecular methodologies used in the process of identifying a disease gene, from the initial stage of study design to the next stage of preliminary locus identification, and ending with stages involved in target characterization and validation. As a volume in the highly successful Methods in Molecular Biology™ series, chapters contain brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and detailed tips on troubleshooting and avoiding known pitfalls. Authoritative and essential, Disease Gene Identification: Methods and Protocols seeks to aid scientists striving toward the identification and characterization of the many disease-related genes, which may someday pave the way for more accurate and improved methods of disease diagnosis as well as vital strategies for disease treatment and prevention.
Technological Issues and Experimental Design of Gene Association Studies -- Statistical Issues in Gene Association Studies -- Identification of Causal Sequence Variants of Disease in the Next Generation Sequencing Era -- Microarray-Based Genome-Wide Association Studies Using Pooled DNA -- Medium-Throughput SNP Genotyping Using Mass Spectrometry: Multiplex SNP Genotyping Using the iPLEX® Gold Assay -- Targeted SNP Genotyping Using the TaqMan Assay -- Bar-Coded, Multiplexed Sequencing of Targeted DNA Regions Using the Illumina Genome Analyzer -- Site-Directed Mutagenesis -- Gene Expression Profiling of Tissues and Cell Lines: A Dual Color Microarray Method -- Methods for microRNA Microarray Profiling -- Allelic Expression Profiling to Dissect Genome-Wide Association Study Signals -- Quantitative Polymerase Chain Reaction: Quantitative PCR Using the Comparative Cq Method -- Genomic Analysis by Oligonucleotide Array Comparative Genomic Hybridization Utilizing Formalin-Fixed Paraffin Embedded Tissues -- RNA Mapping Protocols: Northern-Blot and Amplification of cDNA Ends -- High Content RNA Interference Assay: Analysis of Tau Hyperphosphorylation as a Generic Paradigm -- Integrative Systems Biology Approaches to Identify and Prioritize Disease and Drug Candidate Genes -- Identification of a Common Variant Affecting Human Episodic Memory Performance Using a Pooled Genome-Wide Association Approach: A Case Study of Disease Gene Identification -- RNAi-Based Functional Pharmacogenomics -- Genetic Predisposition to β-Thalassemia and Sickle Cell Anemia in Turkey: A Molecular Diagnostic Approach.
Keywords: Human genetics; Gene expression; Human Genetics; Gene Expression